2021
DOI: 10.1017/s0007123420000472
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Austerity Packages on Government Popularity During the Great Recession

Abstract: During the Great Recession, governments across the continent implemented austerity policies. A large literature claims that such policies are surprisingly popular and have few electoral costs. This article revisits this question by studying the popularity of governments during the economic crisis. The authors assemble a pooled time-series data set for monthly support for ruling parties from fifteen European countries and treat austerity packages as intervention variables to the underlying popularity series. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 69 publications
(57 reference statements)
2
30
0
Order By: Relevance
“…In turn, we expect that the different policy agenda will result in different levels of public support. While both Monti and Draghi began their terms of office with high levels of popularity, it is safe to assume that in the case of Monti the rapid decline was triggered by the austerity policies (see also : Bojar et al 2021). As the Draghi government will be in charge of spending European resources, its popularity is likely to remain relatively high in the longer as well as in the short term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, we expect that the different policy agenda will result in different levels of public support. While both Monti and Draghi began their terms of office with high levels of popularity, it is safe to assume that in the case of Monti the rapid decline was triggered by the austerity policies (see also : Bojar et al 2021). As the Draghi government will be in charge of spending European resources, its popularity is likely to remain relatively high in the longer as well as in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…In public perceptions, it had quickly become an austerity government, one that was, for many, too responsive to 'the demands of European bureaucrats'. As recent research has shown, austerity packages are very likely to undermine governments' popularity (Bojar et al 2021). The Monti government's loss of popularity is thus not necessarily to be attributed to its technocratic nature, but rather to the policies it pursued.…”
Section: Public Opinion: Similar Starting Levels Of Supportmentioning
confidence: 99%
“…In a footnote, Johnston (1999: 505, n10) reports inconclusive results associated with budget balance, while Happy's (1992) vote function model reveals a negative impact of income taxation on aggregate-level incumbency voting from 1953 to 1988. In contrast, several international studies have included fiscal policies, such as taxation, transfers and budget deficits, in their popularity functions (Geys and Vermeir, 2008; Bojar et al, 2021; Jacques and Haffert, 2021). Much remains to be investigated when it comes to the impact of fiscal policy on federal executive approval in Canada.…”
Section: Fiscal Policy Regimes and Public Opinionmentioning
confidence: 99%
“…As such, vote-seeking politicians have a structural incentive to engage in budget deficits, especially as elections approach (Calmfors and Wren-Lewis, 2010). Several studies in comparative political economy confirm that citizens punish governments for aggressive deficit reduction policies (Talving, 2017; Bojar et al, 2021; Jacques and Haffert, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One of the problems with this crisis resolution mechanism is that the austerity measures imposed on crisis countries are highly unpopular (Fernández-Albertos and Kuo, 2016, 2020; Franchino and Segatti, 2019; Jurado et al., 2020) and lead to electoral volatility, public protests, and the emergence of anti-system forces (Bojar et al., 2021; Bremer et al., 2020; Hübscher et al., 2020). Still, existing research shows that voters in most crisis-ridden countries strongly support the euro and are unwilling to leave it despite the costs associated with austerity (Clements et al., 2014; Hobolt and Wratil, 2015; Roth et al., 2016).…”
Section: Introductionmentioning
confidence: 99%